Atuação do enfermeiro no acompanhamento do crescimento e desenvolvimento da criança - Brasil, Samara Keylla Dantas (2013)
The nurses assistance in monitoring the growth and development of children has been characterized mostly a service based on the biological dimension of illness, when in reality, the actions should be combined in the reorientation of care model of the Family Health Strategy. Thus, the research aimed to examine the role of nurses in the growth and development of children. This is an exploratory and descriptive, qualitative approach. The project was approved by the Ethics Committee of the Universidade Federal do Rio Grande do Norte under Opinion No. 191/2012. Data collection was developed in the Health Units from the city of Natal, RN, Brazil. Survey participants were nurses who worked in the Family Health Strategy for at least two years and who performed the monitoring of child growth and development in the health unit selected. Data were collected through an in-depth interview, and seized material from speeches was treated as categorical thematic analysis proposed by Bardin. This process revealed three themes, which were analyzed in the light of Relief Models and Process Work in Health and Nursing and discussed based on the findings literary. The results elucidated that nurses consider their performance satisfactory as it has favored the accession of mothers of children under one year nursing visits, contributing to the reduction of morbidity and mortality due to prevalent diseases, as well as the establishment of a connection between the professionals and mothers. It was shown that despite having a promotion and prevention with the use of lightweight technologies, the nurses also emphasized the care of mothers in complaints and signs and symptoms of children, followed by referrals to professionals in the unit or to other sectors. Furthermore, we found that the process of working nurses face challenges regarding the organizational structure of services and social situation of the family. Given these statements, it is observed that despite the strong interference from hegemonic health model in the performance of nurses, it is found that these professionals have been investing in promotion and prevention to injuries to children in care, with a focus on family context. Thus, nurses are embarking on making the reorientation of health care through the use of relational technologies, which has contributed to solving the integral care to the pediatric population